KEMAMPUAN MENULIS SURAT RESMI SISWA KELAS VII MTs AL-MUTTAQIN PEKANBARU - Nurfadhilah Nurfadhilah; Auzar Auzar; Nursal Hakim (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This research entitled the ability to write official letter of class VII students MTs Al-Muttaqin Pekanbaru. The purpose of this research is to describe the ability to write official letter of class VII of MTs Al-Muttaqin Pekanbaru, and to describe the difference of writing ability of official letter of class VII MTs Al-Muttaqin Pekanbaru in each parallel class between sample groups. The data of this research is the result of the official letter writing skill test of grade VII students of MTs Al-Muttaqin Pekanbaru which is divided into 4 classes and consists of 86 populations with a sample of 71 students. The results of research after testing using T test, the ability to write an official letter equal to the comparison value of 71. Ability to write an official letter of class VII students MTs Al-Muttaqin Pekanbaru classified moderate. Then, tested by using one way anova, to know the difference of ability to write official letter of class VII student of MTs Al-Muttaqin Pekanbaru between sample group. The result is that there is a difference to the ability to write letters between the classes of sample groups.Keywords: abilities, writing, official letters, students